(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In the current Indian literary setting Kamala Dasoccupies a high-flying position as a poetess of talent and creativity. She, amajor Indian poetess in English, has fascinated international attention bydesirable quality of her bold, uninhibited expression of feminine urgesfollowing with other women poets Among the presented Indian female writing inEnglish, Kamala Das’s name ends the list of the writers who have shown seriousapprehension with the representation of woman in literature and have spokenrestiveness with the conventional positioning of woman. Kamala Das’s works show her concern with thesocial and cultural creation of gender, raising her objection against themarginalization and mistreatment of woman.